Photopolymerization of bis-aromatic and alicyclic based solid urethane acrylate macromonomer in the presence of large excess of reactive diluent Kinetics and modeling - Harikrishna, Reghunathan; Ponrathnam, S.; Rajan, C. R.; Tambe, S. S. (Journal of Thermal Analysis and Calorimetry, 2013)
A solid urethane acrylate macromonomer with bis-aromatic as well as alicyclic moieties was synthesized and the kinetics of photopolymerization reactions were studied in the presence of varying concentration of photoinitiator and large excess of reactive diluent using photo DSC. The studies show that the rate of maximum polymerization was found to increase with increase in concentration of photoinitiator while a decrease was observed by an increase in temperature. The final conversion showed a decrease at highest isothermal condition due to vitrification. Estimation of kinetic parameters including applicability of autocatalytic and modified autocatalytic models were investigated by nonlinear regression. It was observed that the modified models gave a better fit with the experimental data and kinetic parameters showed a decrease with increase in temperature and an increase with increase in concentration of photoinitiator.
Keywords: Autocatalytic model; kinetics; Levenberg-Marquardt method; Photopolymerization

Photopolymerization kinetics of bis-aromatic based urethane acrylate macromonomers in the presence of reactive diluent - Harikrishna, Reghunathan; Ponrathnam, S.; Rajan, C. R. (Progress in Organic Coatings, 2014)
The present work deals with the photopolymerization of bis-aromatic based urethane acrylate macromonomers in the presence of excess end capping agent as reactive diluent and estimation of their kinetic parameters. Formulations were made by independently homogenizing the macromonomers with photoinitiators of three different classes. Three different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using photo DSC under polychromatic radiation. The heat flows against time were recorded for all formulations under isothermal condition and the rates of polymerization, peak maximum times as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, formulations with macromonomer containing propoxylated backbone showed higher conversions than the corresponding ethoxylated analogue. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic model are discussed. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bimolecular termination model; kinetics; Macromonomer; Photopolymerization

Reaction kinetics and modeling of photoinitiated cationic polymerization of an alicyclic based diglycidyl ether - Harikrishna, Reghunathan; Ponrathnam, S.; Tambe, S. S. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2014)
Photoinitiated cationic polymerization of cycloaliphatic diepoxides had received tremendous attention, while studies with lesser polymerizable diglycidyl ethers are comparatively less reported. The present work deals with the photoinitiated cationic polymerization of cyclohexane dimethanol diglycidyl ether followed by estimation of kinetic parameters. The effects of concentration of photoinitiator and temperature on curing performance were studied using photo differential scanning calorimeter or photo DSC with polychromatic radiation. It was observed that the rate of polymerization as well as ultimate conversion increased with increasing concentration of photoinitiator and temperature. The influences of gelation as well as diffusional restrictions have remarkable effect on cure performance. The kinetic parameters as per autocatalytic kinetic model were studied by Levenberg-Marquardt nonlinear regression method instead of conventional linear method for obtaining more accurate values of apparent rate constant. It was observed that the model fits with data from initial stages to almost towards the end of the reaction. The activation energy was found to be higher than the values reported for more reactive cycloaliphatic diepoxides. The value of pre-exponential factor increased with increase in activation energy showing influence of gelation at early stages of reaction. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Autocatalytic model; kinetics; Levenberg-Marquardt method; Photopolymerization